2019
DOI: 10.1016/j.jmb.2019.01.028
|View full text |Cite
|
Sign up to set email alerts
|

RNA as a key factor in driving or preventing self-assembly of the TAR DNA-binding protein 43

Abstract: Amyotrophic lateral sclerosis and frontotemporal lobar degeneration are incurable motor neuron diseases associated with muscle weakness, paralysis and respiratory failure. Accumulation of TAR DNA-binding protein 43 (TDP-43) as toxic cytoplasmic inclusions is one of the hallmarks of these pathologies. TDP-43 is an RNA-binding protein responsible for regulating RNA transcription, splicing, transport and translation. Aggregated TDP-43 does not retain its physiological function. Here, we exploit the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 71 publications
13
93
0
Order By: Relevance
“…Removal of the RBD reduces the liquid-like behaviour of the condensate 22 in favour of interactions that lead to more solid-like aggregation 29,73 . In agreement with this finding, previous studies indicated the importance of RNA in SGs network specificity and organization 74 : RNA-binding proteins can be dragged in the condensates by RNA networks 31,37,75 . Indeed, RNA is a key modulator of the dynamics and material state of ribonucleoprotein complexes 70,76,77,78 and a highly structured RNA can provide the scaffold to allow formation of large assemblies 20,31 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Removal of the RBD reduces the liquid-like behaviour of the condensate 22 in favour of interactions that lead to more solid-like aggregation 29,73 . In agreement with this finding, previous studies indicated the importance of RNA in SGs network specificity and organization 74 : RNA-binding proteins can be dragged in the condensates by RNA networks 31,37,75 . Indeed, RNA is a key modulator of the dynamics and material state of ribonucleoprotein complexes 70,76,77,78 and a highly structured RNA can provide the scaffold to allow formation of large assemblies 20,31 .…”
Section: Discussionsupporting
confidence: 83%
“…There is an intense debate on which protein regions contribute to the assembly and dynamics of biomolecular condensates 30,31,37,69,70,71,72 . Our computational analysis of H. sapiens and S. cerevisiae proteomes reveals that the PS propensity is intrinsically linked to occurrence of PrLDs and RBDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study using a combination of biophysical approaches showed that both sequence and length of RNA can influence TDP-43 aggregation. Specifically, long UG repeats may help stabilize TDP-43 structure while excess non-specific RNA may promote aggregation (Zacco et al, 2019). Taken together these studies underscore the importance of a thorough characterization of the different TDP-43 conformations in the context of its RNA and protein partners.…”
Section: Rna As a Toxic Factormentioning
confidence: 87%
“…Others have shown that the CTD is not sufficient, but rather that the CTD combined with the RRM2 is required for significant accumulation of aggregates in cellular models (Johnson et al, 2008;Yang et al, 2010;Fallini et al, 2012;Wang et al, 2013). And indeed, as discussed above, the RRM domains contain amylogenic sequence elements that contribute to aggregation (Shodai et al, 2012(Shodai et al, , 2013Chiang et al, 2016;Guenther et al, 2018b) and constructs lacking the CTD have been shown to aggregate as well (Zacco et al, 2019).…”
Section: Liquid-liquid Phase Separation and Aggregationmentioning
confidence: 98%